The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1182/blood-2019-127094
|View full text |Cite
|
Sign up to set email alerts
|

Peak Lymphocyte Count after CAR T Infusion Is a Clinically Accessible Test That Correlates with Clinical Response in Axicabtagene Ciloleucel Therapy for Lymphoma

Abstract: Background: Two-year follow-up from ZUMA-1 trial for axicabtagene ciloleucel (axi-cel) CD19 chimeric antigen receptor T-cell (CART) in aggressive non-Hodgkin lymphoma (NHL) demonstrated that patients (pts) achieving complete remission (CR) as their best response have the longest progression free survival (PFS), while PFS remained poor for others. Majority of the best response are achieved by month 3 post-infusion. Moreover, a subset of pts who do not achieve CR by month 1 may still achieve CR while others will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In particular, the modeled persistence level of memory CAR-T cells is positively correlated to the CAR-T peak level, in line with recent findings that patients with positive ddPCR (indicative for persistence) at six months had a significantly higher median peak of CAR-T cell copies compared with negative ddPCR [33]. Also, the minimal tumor burden is inversely related to the CAR-T cell peak level, consistent with [34], which reported that higher peaks of CAR-T cells within 15 days are associated with increased likelihood of achieving complete remission.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the modeled persistence level of memory CAR-T cells is positively correlated to the CAR-T peak level, in line with recent findings that patients with positive ddPCR (indicative for persistence) at six months had a significantly higher median peak of CAR-T cell copies compared with negative ddPCR [33]. Also, the minimal tumor burden is inversely related to the CAR-T cell peak level, consistent with [34], which reported that higher peaks of CAR-T cells within 15 days are associated with increased likelihood of achieving complete remission.…”
Section: Discussionsupporting
confidence: 88%
“…The CCR7+:CCR7-T-cell ratio was positively associated with CAR T-cell peak and cumulative expansion during the first month after infusion. More robust CAR T-cell expansion was also associated with a higher likelihood of achieving CR (11), and early expansion of a specific subset of CD4+ CAR T cells (i.e., with high expression of CD45RO, CD57, PD1, and T-bet transcription factor) may help identify patients most likely to maintain CR at 6 months (12).…”
Section: Axi-cel For Aggressive B-cell Lymphoma Efficacy and Predictomentioning
confidence: 98%
“…The lymphocyte count captures the magnitude of CAR T-cell proliferation in vivo, an early aspect of CAR T-cell kinetics associated with both durable remission and risk of toxicity. 47 A study conducted by Novo et al 58 determined a statistically significant difference in peak absolute lymphocyte count between those experiencing and not experiencing complete response.…”
Section: Direct Car T-cell Detection Methodsmentioning
confidence: 99%
“…The lymphocyte count captures the magnitude of CAR T‐cell proliferation in vivo, an early aspect of CAR T‐cell kinetics associated with both durable remission and risk of toxicity 47 . A study conducted by Novo et al 58 determined a statistically significant difference in peak absolute lymphocyte count between those experiencing and not experiencing complete response. The measurement of immunoglobulin levels is not frequently utilised, owing to disease‐ and therapy‐ related hypo‐gammaglobulinaemia being an important confounding factor 47 .…”
Section: Evaluation Of Car T‐cellsmentioning
confidence: 99%